Recent change in surface mass-balance trends of glaciers on James Ross Island, north-eastern Antarctic Peninsula - Zbyněk Engel; Kamil Láska; Jana Smolíková; Jan Kavan (Journal of Glaciology)
Glaciers cover 132 900 km2 around the Antarctic Ice Sheet, but few are subject to annual mass-balance measurements. Lookalike Glacier and Davies Dome on James Ross Island have been monitored since 2009, providing the third longest mass-balance record for the northern Antarctic Peninsula. These glaciers had a balanced mass budget over the period 2009/10–2014/15 but started to lose their mass thereafter. Between 2014/15 and 2020/21, mass change rates were −0.15 ± 0.13 and −0.26 ± 0.11 m w.e. a−1 for Lookalike Glacier and Davies Dome, respectively. The mean equilibrium-line altitudes over this period at Lookalike Glacier (362 ± 18 m a.s.l.) and Davies Dome (>427 ± 22 m a.s.l.) are 51 and >34 m higher compared to the previous 6-year period. The mean accumulation area ratio values determined for the period 2014/15–2020/21 are lower than the balanced-budget ratio indicating that glaciers are out of balance with the current climate. The data confirm the transition from positive to negative mass-balance periods around 2014/15, which is attributed to the change in air temperature trends. The mean summer temperature increased by 0.9°C between the periods 2009/10–2014/15 and 2015/16–2020/21 and melt-season temperatures became predominantly positive.